PENINGKATAN KETERAMPILAN BERPIKIR KRITIS MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA KELAS IV SEKOLAH DASAR - Elsah Isnaini; Hendratno; Mahallisa Dyah Pristanti; Dwi Ristavida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve students' critical thinking skills in learning Indonesian through the application of the Problem Based Learning model with a Culturally Responsive Teaching approach in class IV-D at SDN Kedurus III/430 Surabaya. This type of research is collaborative classroom action research (PTKK). This research was carried out over two cycles which included planning, implementation, observation and reflection. Data collection techniques use observation and written tests. The subjects of this research were students in class IV-D at SDN Kedurus III/430 Surabaya, totaling 26 students. The resulting data shows an increase in critical thinking skills which can be proven by the results for two cycles. In the implementation of cycle I, the average percentage result was 56.15%, while cycle II obtained the average percentage result of 82.3%, resulting in an increase of 26.15%. Based on the presentation of these results, it can be concluded that the results of this research show that critical thinking skills by applying the Problem Based Learning model with a Culturally Responsive Teaching approach have increased significantly. This can be seen from the increase in the average percentage from cycle I and cycle II in class IV-D at SDN Kedurus III/430 Surabaya with information material, characters and problems in the odd semester stories of the 2024/2025 academic year.